DELIVERING MESSAGES THROUGH COMIC STRIP AS LEARNING MEDIA: An Analysis of Message Forms - Fitria Iswari (FKIP, Universitas Banten Jaya, 2021)
Communication is an activity that cannot be stopped in human life. Especially during the Covid -19 pandemic, face-to-face communication is difficult. This is also quite influential in the world of education where during the Covid -19 pandemic there were many face-to-face meetings between lecturers and students through virtual face to face. In the learning process, sometimes students are embarrassed or reluctant to express their opinions. In this study, researchers tried to use comic strip learning media as a medium for conveying opinions from students. This study used qualitative method with data collection obtained from the analysis of the form of messages from comic strip was made by students. The purpose of this study is to determine the types of messages made by students through comic strip media with educational themes. From the data, it shows that 21 comic strips have informative messages, namely 52.5%, and 19 comic strips that have persuasive form messages or 47.5% of the percentage. While the coercive message form shows the number 0. From this study it can be concluded that comic strips can be an alternative learning medium in the process of delivering messages or opinions.